2020
DOI: 10.24815/jks.v20i3.18732
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian infeksi soil-transmitted helminth pada petani

Abstract: Abstrak. Petani memiliki risiko terinfeksi Soil-Transmitted Helminth (STH) akibat sering berkontak langsung dengan tanah yang terkontaminasi oleh telur STH. Tingginya risiko terinfeksi STH pada petani berhubungan dengan perilaku personal hygiene dan pemakaian alat pelindung diri saat bekerja. Tujuan dilakukan penelitian untuk mengetahui angka kejadian infeksi STH dan faktor yang mempengaruhinya. Penelitian dilaksanakan di Kelurahan Pinang Jaya, Lampung. Populasi pada penelitian ini  adalah 63 petani dan sampel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…This result supports a previous study showing that the highest intensity of hookworm infection was found in adults and agricultural workers (1). Another study on farmers in Bandar Lampung also showed that the worm that infected farmers the most was hookworm (13 farmers, 59.1%) (7). Research on agricultural communities in the Bolivian Amazon also showed that the species that infected the most agricultural communities was the hookworm (83%) (16).…”
Section: Figure 8 Overlay Map: Geohelminth Contaminated Soil Buffer A...supporting
confidence: 86%
See 1 more Smart Citation
“…This result supports a previous study showing that the highest intensity of hookworm infection was found in adults and agricultural workers (1). Another study on farmers in Bandar Lampung also showed that the worm that infected farmers the most was hookworm (13 farmers, 59.1%) (7). Research on agricultural communities in the Bolivian Amazon also showed that the species that infected the most agricultural communities was the hookworm (83%) (16).…”
Section: Figure 8 Overlay Map: Geohelminth Contaminated Soil Buffer A...supporting
confidence: 86%
“…Research conducted on plantation workers in July showed that nine out of 36 people (25%) were infected by geohelminths (6). Another study on farmers in Bandar Lampung explained that as many as 22 people (40%) were positively infected with STH (7). Several risk factors are associated with geohelminth infections among farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted (Saftarina et al, 2020), 52.6% of farmers who did not wear PPE completely were infected with STH, and of farmers who wore PPE completely, only 11.8% were infected. This research is in line with research conducted by (Baidowi et al, 2019) in the Kaliputih Plantation, Sumber Bulus Village, Ledokombo sub-district, Jember district, that as many as 91.67% of workers use PPE well, and 8.33% use PPE poorly.…”
Section: In Use Of Ppementioning
confidence: 99%
“…This STH infection can disrupt the tissue and organs of the sufferer's body by taking nutrients from the body (Kurniawan et al, 2023). Farmers are at significant risk of soil-transmitted Helminth (STH) infection because farmer workers always have direct contact with soil contaminated with STH egg cells (Saftarina et al, 2020). The cause of STH infection is poor personal hygiene in farmers, such as not wearing footwear when doing activities outside the home and not wearing PPE in the form of closed footwear when working (Saftarina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia berada di posisi ke-2 menjadi negara dengan kejadian infeksi STH tertinggi di Asia Tenggara. Kejadian infeksi tinggi di indonesia karena adanya iklim tropis dan juga kelembaban sehingga dapat mendukung penyebaran infeksi cacing (Saftarina et al, 2020).…”
Section: Pendahuluanunclassified